Rancang Bangun Game Edukasi Ular Tangga Pajak (ARTAJAK) sebagai Media Interaktif untuk Menarik Kesadaran Pajak Anak Sekolah Dasar - Elsa Apriani; Rahmi Imanda; Hafizh Dhery Al Assyam; Atsna Virayani Yusriy Widarey (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2023)
In this era of the 4.0 industrial revolution, there are still many people who lack understanding about taxes. Due to this situation, early tax education is highly necessary. Because of the limited comprehension among children regarding the significance of the role of taxes, it greatly influences national development. Therefore, the objective of this research is to educate elementary school children through the creation of a snake-and-ladder game accompanied by quizzes about basic tax concepts. The development of this game employs the prototype research method as it helps developers work with users to effectively define system requirements, thereby minimizing system errors from the outset. The results of creating this game indicate that the developed game is able to enhance users' insights into tax knowledge and has been field-tested by 5 elementary school students to assess the success of the created ARTAJAK game.